人工膝関節再置換例の検討 - SHIRAKATA Haruo; 間島 直彦; 渡部 昌平; 今井 浩; 藤井 裕子; 山本 晴康 (Japanese Journal of Rheumatism and Joint Surgery, 2003)
Here we report twelve cases of revision total knee arthroplasty (TKA) done in Ehime University Hospital.Twelve revision TKA procedures were performed between 1991 and 2001; four of these were performed on men and eight on women. The average age of the patients was 71.8 years. Originally, ten of these cases had been diagnosed as osteoarthritis of the knee, one as rheumatoid arthritis, and the other as a bone tumor of the distal end of the femur. Among the twelve were seven cases of metalosis, three of infection, one of aseptic necrosis of unknown origin, and one of implant failure following reimplantation.At present, all patients are pain-free and walk with a slight limp, with or without a stick. In patients who had an infection, there has been no recurrence of the infection.When revision TKA is performed, using accurate technique, covering the bone deficits, and soft-tissue balancing are important. In patients who have joint instability, a stem or rotator hinge type TKA must be used. Sufficient pre-operative planning should, therefore, be conducted.